Cryptanalysis of Secure ECC-Based Three Factor Mutual Authentication Protocol for Telecare Medical Information System - C. Madan Kumar; Ruhul Amin; M. Brindha (Cyber Security and Applications, 2023)
Telecare Medical Information System (TMIS) is gaining importance in the present COVID-19 crisis. TMIS as a technology, offers patients a range of remote medical services, incorporated into Wireless Body Area Network (WBAN). The patient’s medical report is confidentially transmitted over an open channel in TMIS environments. An attacker may attempt to compromise the security, such as forgery, replay, and impersonation attacks. To ensure secure communication, various authentication solutions have been introduced for TMIS. Biometrics and Elliptic Curve Cryptography-based mutual authentication protocol was recommended by Sahoo et al. (2020) and is proved to have some loopholes in the protocol. We discovered, however, Sahoo et al. method is unable to prevent privileged insider attacks and insider attacks along with patient anonymity. Jongseok Ryu et al. recommended a ECC based three-factor mutual authentication protocol and ensures patient’s confidentiality for TMIS with proof of informal analysis. They have also performed formal security studies utilizing the Automated Validation of Internet Security Protocols and Applications (AVISPA), the Burrows–Abadi–Needham (BAN) logic and Real-Or-Random (ROR) model. However, we have reviewed the Jongseok Ryu et al.’s proposal. Based on his attacker model, we have examined that this scheme is unsafe against Message Substitution Attacks, Man-in-the-Middle attacks, Session Key Disclosure attacks, Privileged Insider attacks, and Stolen verifier attacks. we suggest a technique to be safe from the above security threats.